The Impact of Employee Motivation Approaches on Achieving Competitive Advantage: Case of Banking Sectors in Pekan baru, Indonesia - Muhammad, Arif Radhian (2011)
This study identifies the existing relationship between employee motivation approaches and competitive advantage. The role of employee motivation approaches have become important activities of Human Resource Management where employee motivation approaches can effect on employees’ behavior and attitude to achieve organization’s goals. This study was conducted in Pekan baru, Indonesia as geographical location where this study was involving employees who in 4 selected banks. This relationship has been investigated by using SPSS. The results indicated a significant relationship between employee motivation approaches and competitive advantage.